2021
DOI: 10.20849/ijsn.v6i1.834
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effectiveness of Share Decision Making and Standard Education for Cardiac Catheterization: A Pilot Study

Abstract: Background: Cardiovascular diseases are the second leading cause of death in the top ten leading causes of death in 2018 in Taiwan, and coronary artery disease is one of the main causes.Aim: To compare whether there are differences in patient knowledge, anxiety, and satisfaction between the utilization of patient decision aid for cardiac catheterization and routine health education.Subject and methods: Between July 2020 and September 2020, subjects were recruited in the clinics of the Department of Cardiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…These results are consistent with those reported in Breda & Cerejo (2021) who showed that health education can enhance patient satisfaction. Furthermore, Chiu et al(2021) and Goodman et al (2021) who examined the effect of educational programs on patient satisfaction concluded that the experimental group more satisfied with the educational program delivered. Additionally, Piotrkowska et al(2021) revealed that continued health teaching increased patient satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…These results are consistent with those reported in Breda & Cerejo (2021) who showed that health education can enhance patient satisfaction. Furthermore, Chiu et al(2021) and Goodman et al (2021) who examined the effect of educational programs on patient satisfaction concluded that the experimental group more satisfied with the educational program delivered. Additionally, Piotrkowska et al(2021) revealed that continued health teaching increased patient satisfaction.…”
Section: Discussionmentioning
confidence: 98%